Genome-Wide Mapping of Transcriptional Regulation and Metabolism Describes Information-Processing Units in Escherichia coli - Ledezma-Tejeida, Daniela; Ishida, Cecilia; Collado-Vides, Julio (Frontiers in Microbiology, 2017)
In the face of changes in their environment, bacteria adjust gene expression and produce an appropriate response. The individual layers of this process have been widely studied: the Transcriptional Regulatory Network describes the regulatory interactions that produce changes in the Metabolic Network, both coordinated by the Signaling Network; but the interplay between them has never been described in a systematic fashion. Here, we formalize the process of detection and processing of environmental information mediated by individual transcription factors in a concept termed Genetic Sensory Response Unit (GENSOR Unit), composed of four components: 1) signal, 2) signal transduction, 3) genetic switch, and 4) response. We used experimentally validated datasets from two databases to assemble a GENSOR Unit for each of the 189 local Transcription factors of Escherichia coli K-12 present in RegulonDB. Further analysis suggested that feedback is a common occurrence in signal processing and showed a gradient of functional complexity in the response mediated by each Transcription factor, as opposed to a one regulator-one pathway rule. Finally, we provide examples of other GENSOR Unit applications such as hypothesis generation, detailed description of cellular decision-making and elucidation of indirect regulatory mechanisms.